Green transportation system - Rahman, Mohammed Ataur; Rafia, Afroz; Jaafar, Abdul Hassan (IIUM Press, International Islamic University Malaysia, 2020)
The Green Transportation means any kind of transportation vehicle that is eco-friendly and does not have any negative impact on the social, environmental and climate impacts and the ability to, in the global scope, supply the source energy indefinitely. The current transportation systems come along with a wide range of problems including global warming, environmental degradation, health implications, and emission of greenhouse gases. In fact, the transport sector attributes to 23% of the globe’s greenhouse gas emission resulting from the burning of fossil fuels. Out of the total greenhouse gas emissions, road transport takes up a lion share, 75% to be precise and this trend is projected to increase in the future if it continues unabated. The greenhouse gasses have been associated with rising cases of cancer and other cardiovascular diseases. The emissions produced by green vehicles are not harmful to human health, so embracing green transportation would only improve a nation’s health status. The emissions produced by green vehicles are not harmful to human health, so embracing green transportation would only improve a nation’s health status. Green transportation revolves around the efficient and effective use of resources, modification of the transport structure and making healthier travel choices. Promising innovative technologies could be the ultimate solution, but the innovations come to fruition if the world can play a significant role in the development of the transportation system. Manufacturing and distribution of green vehicles could go along with improving existing transport systems. This would lead to the creation of more jobs in the transport sector, hence, minimizing social-economic disparities and building up a sustainable economy. Transportation sustainability is largely being measured by transportation system effectiveness and efficiency as well as the environmental and climate impacts of the system. Short-term activity often promotes incremental improvement in fuel efficiency and vehicle emissions controls while long-term goals include migrating transportation from fossil-based energy to other alternatives such as renewable energy and use of other renewable resources. The entire life cycle of transport systems is subject to sustainability measurement and optimization. This is a comprehensive book presents green transportation system including the evaporative battery thermal management system of the electric and hybrid electric vehicles, wireless battery charge balancing system, advanced charging system, and electromagnetic transmission system which are key elements of the green transportation system. This book consists of nine chapters. Chapter 1 basically gives a brief review of each chapter of the book. Chapter 2 presents the Malaysian perception toward the green transportation based on a conducted survey. Chapter 3 presents the development of a fuzzy controlled evaporative battery cooling thermal management system (EC-BThMS) to maintain the battery temperature in the desired range. The proposed system has been developed for estimating the total cooling loads and thermal behaviour of the battery cells. This topic is continued in Chapter 4, where wireless monitoring system is introduced. This chapter discussed in detail about the charge balancing between the cells of the battery pack in order to prolong their shelf life. An advanced electric vehicle charging system with three modes is presented in Chapter 5. The slow charging mode is proposed for residence, medium charging mode for office parking lots, and fast charging mode for charging station on the road. With three modes charger topology, consumers could choose a suitable mode for their car based on the need. Chapter 6 presented the development of an electric coaster theoretically and practically. A vehicle dynamic analysis is used to obtain an optimum size of vehicle battery pack and suitable size for the vehicle traction motor. A comprehensive procedure of the ICE Mercedes Benz conversion to electric coaster is presented in this chapter. The electrification of the vehicle is continued in Chapter 7, where the development of an electromagnetic actuator for continuous variable transmission (CVT) is presented. The system is considered as the replacement of the conventional hydraulic actuated CVT system. The newly developed system is able to make the car accelerate faster with minimum problems. Moreover, this book presents the technology for the energy independent electric vehicles. The review of the prospects of energy technology for vehicle’s body builds with nano/micro filler epoxy resin (ER) sandwiched by carbon fibre (CF) and lithium (Li) plate is presented in Chapter 8. The studied on the electrical charge storage capacity for different percentage of micro filler ER has been presented in this chapter. The role of this technology is to store the power and discharge as auxiliary power whenever the power system of the car is necessary. The new technology could contribute on take away car weight, reduce the excessive loads of the main battery pack to meet the power demand of the car and reduce the emission. The materials included in this book have been used in undergraduate and postgraduate studies in the course of vehicle dynamics and electric and hybrid electric vehicle that I have been teaching at International Islamic University Malaysia. I have been used the evaporative battery thermal management system in the IIUM Electric Car for the battery pack cooling, which helps me to get the outstanding award in PROTON Green Mobility Challenge, 2012. It has also been presented, in part, at the FISITA in Beijing, China, ASME in Boston, USA and the Military Institute of Science and Technology (MIST), Dhaka, Bangladesh.